2010
DOI: 10.1074/jbc.m110.174391
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent Prion Protein Misfolding and Neurotoxicity

Abstract: Prion diseases are neurodegenerative disorders caused by misfolding of the normal prion protein (PrP) into a pathogenic "scrapie" conformation. To better understand the cellular and molecular mechanisms that govern the conformational changes (conversion) of PrP, we compared the dynamics of PrP from mammals susceptible (hamster and mouse) and resistant (rabbit) to prion diseases in transgenic flies. We recently showed that hamster PrP induces spongiform degeneration and accumulates into highly aggregated, scrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 42 publications
8
51
0
Order By: Relevance
“…Whole-mount immunohistochemistry of fixed larval brains was conducted by fixing in 4% formaldehyde, washing with PBT, and blocking with 3% bovine serum albumin before incubating with the primary antibody as described previously (Fernandez-Funez et al, 2010). We incubated first with the 6H4 anti-PrP antibody (1: 1,000) followed by the secondary antibody anti-mouse-Cy3 (Molecular Probes) at 1:600.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole-mount immunohistochemistry of fixed larval brains was conducted by fixing in 4% formaldehyde, washing with PBT, and blocking with 3% bovine serum albumin before incubating with the primary antibody as described previously (Fernandez-Funez et al, 2010). We incubated first with the 6H4 anti-PrP antibody (1: 1,000) followed by the secondary antibody anti-mouse-Cy3 (Molecular Probes) at 1:600.…”
Section: Methodsmentioning
confidence: 99%
“…We and others showed previously that mouse PrP (MoPrP)-WT induces progressive toxicity in locomotor neurons associated with the accumulation of pathogenic conformations (Fernandez-Funez et al, 2010; Gavin et al, 2006). In contrast, MoPrP-N159D has lower turnover than MoPrP-WT, suggesting that Drosophila cells can detect aberrant structural features on MoPrP-WT and promote its degradation.…”
Section: Introductionmentioning
confidence: 99%
“…PrP fractions were prepared from fly head homogenates by a method adapted from Fernandez-Funez et al (50). A volume of fly head homogenate that was equivalent to 20 fly heads was mixed with 20 l of 10% (wt/vol) Sarkosyl (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…72 By using transgenic flies, Fernandez-Funez et al demonstrated that misfolding and neuro-toxicity of wildtype PrP are sequence-dependent: hamster PrP formed larger amounts of PrP aggregates and induced spongiform degeneration, whereas rabbit PrP formed only very smaller amounts of PrP aggregates and did not induce spongiform degeneration. 73 Remarkably, the same study also found that although small amounts of PrP aggregates were also detected in young flies (day 1) expressing hamster PrP, spongiform degeneration was not evident. Therefore, the small amounts of PrP aggregates were unable to induce spongiform degeneration.…”
Section: Insoluble Prp C and Alzheimer Diseasementioning
confidence: 52%